Muladíes. Lectura política de una conversión: los Banū Qāsī (714-924). A Political Reading of Religious Conversion: The Case of the Banu Qasi (714-924) - Pavón Benito, Julia (Anaquel de Estudios Árabes, 2006)
This paper aims to provide a political synthesis and reading —not a complete historical development— of the lineage of Banū Qāsī, a distinguished family that converted to Islam and collaborated with Cordoba in the Superior Mark. The main objective of this paper is to clarify their political and social position in the population and geographical situation of Al-Andalus.